Biocoenotic connections between lixinae-weevils (Сoleoptera: Curculionidae: Lixinae) and the zoophages - S.V. Volovnik (Кавказский энтомологический бюллетень, 2011)
Original data on the lixinae beetles as preys of spiders, ants, beetles are given. Ants settle in the cavities gnowed by lixine weevils in the stems and roots. Ants feed the juice that exudes on the leaves after lixine imagoes gnowing. Literary data on the lixinae beetles as preys of insects, amphibians, reptilians, birds and mammals are summarized. These weevils are accidental preys for zoopages owing to low quantity, low density and some features in its morphology and behavior (except Cleonis pigra (Scopoli, 1763) and Asproparthenis punctiventris (Germar, 1824) that sometimes are numerous). Apparently, main natural enemies of lixine are specialized parasites.